Factors of susceptibility to online romance scam in Malaysia: unraveling the complex pathways - Purwaningrum, Evi Kurniasari; Ho, Yi Ming; Imawati, Diana; Prihadi, Kususanto Ditto; Talib, Mansor Abu (Intelektual Pustaka Media Utama, 2024)
In this cross-sectional study, we delve into the multifaceted realm of online scam victimization by investigating a diverse array of individual factors that may predispose adults to fall prey to online scams. The central objective of this research is to ascertain the strongest predictor among the following variables: loneliness and the sense of mattering and to elucidate the moderating effect of social media engagement (SME) on the relationship between these predictors and online romantic scam (ORS) susceptibility (OSS). A sample of 380 adults aged 18 to 65 years (M=33.4) participated in this study to respond to demographic questionnaires and scales of the respective variable. The results suggested that the direct effect of relationship satisfaction on ORS susceptibility is not significant without the serial mediation roles of loneliness and mattering at a high level of SME. Further implications, limitations, and suggestions are discussed.